The controversy of klotho as a potential biomarker in chronic kidney disease - Yu, Li-Xia; Li, Sha-Sha; Sha, Min-Yue; Kong, Jia-Wei; Ye, Jian-Ming; Liu, Qi-Feng (Frontiers in Pharmacology, 2022)
Klotho is an identified longevity gene with pleiotropic kidney beneficial effects. Emerging evidence revealed that the decline in Klotho level is demonstrated in early chronic kidney disease (CKD) and continues as CKD progresses. Klotho deficiency was also linked to increased dismal outcomes or CKD mineral bone disorders (CKD-MBD). Thus, Klotho has been proposed biomarker candidacy in CKD diagnosis or prognosis evaluation in this patient population. Nevertheless, available clinical data on the clinical significance of Klotho regarding the relationship between Klotho with kidney function, CKD stages, adverse kidney or non-kidney outcomes and CKD-MBD is still inconsistent or even contradictory, which challenges the effectiveness of Klotho in clinical practice at the present time. Although the current uncertainty does not preclude necessarily the clinical significance of Klotho, a general consensus in this area is still not reached. Thus, this concern should be addressed and the potential sources of the controversies should be summarized and investigated. Yet a review which systematically examined the controversy of Klotho as a potential biomarker in CKD's diagnosis, prognosis and CKD complication is still lacking. Therefore, this study aims to discuss the above discrepancies and analyze the potential causes behind from the view point of Klotho's clinical application. We firstly collected the present clinical inconsistent findings based on the relationship of Klotho with CKD stages, renal or non-renal adverse outcomes and CKD-MBD in human studies. Then, we furtherly addressed and analyzed the underlying sources of the controversies, and finally highlighted future directions to resolve these disagreements prior to applying Klotho into clinical practice in CKD.